Quantifying yield gaps for rain-fed maize (Zea Mays) in South Africa: A bottom-up approach - Mandigora, Brian George (Stellenbosch : Stellenbosch University, 2018)
Thesis (MScAgric)--Stellenbosch University, 2018.